Assessment of customer satisfaction with logistics service in the light of the results of the research - Kułyk Piotr; Michałowska Mariola; Kotylak Sławomir (Management, 2017)
In an era of rapidly growing competition logistic customer service is growing increasingly important and is becoming a substantial factor in the success of companies operating in the market. Therefore, it is necessary to improve the components affecting the quality of customer service. Taking appropriate action in this regard, and thus preparing and implementing an appropriate logistic customer service strategy becomes important from the point of view of both the survival and development of enterprises, and to achieve sustainable competitive advantage. The aim of this study is to identify and evaluate determinants influencing consumers′ purchasing decisions in the area of logistics customer service. In addition, the article focuses on the development of solution proposals for enterprises to enable a better match the supply to the needs and preferences of customers. It is worth noting that the effectiveness and efficiency of operations in the field of logistic customer service is highly dependent on proper identification of needs and expectations of existing and potential buyers. Therefore, there is in this respect a need for permanent monitoring of the quality of service and customer expectations.